Case Study: Designing a 40 Storey High Office Building Using two Variants, with Regular Concrete Columns and with Compound Ultra-High Performance Concrete Columns and Regular Concrete Columns. (2016) - Popa, Mircea; Kiss, Zoltan; Constantinescu, Horia; Bolca, Geanina
Abstract: The problem of having less and less space and of shortening distances results in urban agglomerations on small surfaces of land. Therefore, it is obvious that the future is that of very high, slender buildings, with unusual and daring shapes. These structures incorporate new and ever more efficient materials, faster lifts, more and more complex design methods and special execution technologies. Globally, there a real competition between developed economies for obtaining the record of having the tallest building on earth. Because columns are an essential component of these high structures, the addressed subject is of global interest. The design of a 40 storey office building is being proposed, using two variants, namely having two different types of columns: simple section – regular columns made of regular concrete (RC) class C 35/45 and compound section – columns with the core made of ultra-high performance concrete (UHPC) and an outer shell made of regular concrete (RC) also class C 35/45. The differences in economy and section between the two proposed variants will be analysed.